DISCOURSE ON MOVEMENT AND THE THEORY OF TRANSUBSTANTIAL MOVEMENT OF MULLĀ ṢADRĀ IN THE PROCESS OF PERFECTION OF THE SOUL - Walid, Kholid Al (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2024)
Motion is a natural law that both physicists and philosopher’s study. Physicists persistently pursued the concept of motion, but motion in modern science is only elaborated as a material natural phenomenon so do the Greek and peripatetic philosophers in the Islamic philosophy tradition. The fundamental question this article wants to answer is whether motion is only limited to material and accidental as believed by Physicists and Greek and peripatetic philosophers in the Islamic philosophy tradition. Mullā Ṣadrā, the philosopher of muta‘āliyah wisdom, shows evidence that motion is not limited to these two things but also occurs at the substance level (al-ḥarakah al-jawhariyyah). The problem in this case, which is also related to the Soul as the Substance of the human self is whether the soul experiences motion and if the soul experiences motion, what kind of motion happens to it. To answer this, a literature study was conducted using an analytical argumentative approach commonly used in philosophical research. Based on the evidence used by Mullā Ṣadrā, it can be proven that the movement is not only limited to the accidental level but also the substance level besides the soul experiences movement, which is the movement of perfection in the physical and spiritual as well as in the world and afterlife.